Dari Kitab ke Klik: Literasi Moderasi Beragama Pondok Pesantren di Dunia Digital - Khodafi, Muhammad; Zulaili, Iin Nur; Taufiqurrohman, Taufiqurrohman; Kurniawan, Adib (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
This qualitative research explores the relationship between Islamic boarding schools and Ngaji Online in the digital realm. This research aims to identify the diversity of Turats books in Indonesian Islamic boarding schools, analyze Islamic boarding school Turats studies expressed in the digital space, and explain studies of religious moderation in Islamic boarding school Turats in the digital space. This research uses the Netnography method which places digital society ethnographically. However, to explain the connection with Turats pesantren, the initial data analyzed is the tradition of studying the Turats book in several Salaf, modern, and Salafy Islamic boarding schools, one aspect of constructing Islamic boarding school cultures. The results of this research indicate that there are quite significant differences between each Islamic Boarding School which is the object of research. The Turats studies taught in Islamic boarding schools are also presented online via each Islamic boarding school's social media.